Nitrogen content, nitrate reductase activity, and biomass of kimpul (Xanthosoma sagittifolium) on shade and nitrogen fertilizer variation - ISNAINI CHOIRUL LATIFA; ENDANG ANGGARWULAN (Smujo International, 2009)
Abstract. Latifa IC, Anggarwulan E. 2009. Nitrogen content, nitrate reductase activity, and biomass of kimpul (Xanthosoma sagittifolium) on shade and nitrogen fertilizer variation. Nusantara Bioscience 1: 65-71. The aims of this research were to study the effect of shade and nitrogen fertilizer variation and also their interaction to nitrogen content, nitrate reductase activity, and biomass of kimpul (Xanthosoma sagittifolium (L.) Schott.). This research was arranged in randomized complete block design (RCBD) with two factor, they were shade variation which contained 3 levels (0%, 50%, and 75% of shade) and nitrogen fertilizer dosage variation which contained 4 levels (0; 0.0625; 0.125; dan 0.25 g ZA/kg of soil of the dosage of ZA fertilizer). The variables of the research were nitrogen content, nitrate reductase activity, fresh weight, dry weight, and shoot/root ratio. The collected data were analyzed with General Linear Model Univariate, and continued with Duncan's Multiple Range Test (DMRT) on 5% significantly levels. The result showed that the shade treatment affected nitrogen content, fresh weight, and shoot/root ratio. The fertilizer application and the interaction between shade and fertilizer application were affected to all variables. The treatment of 75% shade and 0.25 g ZA/kg of soil of ZA fertilizer dosage increased nitrogen content (5.32%) and fresh weight (420.88 g). The treatment without shade and 0.25 g ZA/kg of soil, dosage of ZA fertilizer increased nitrate reductase activity (260.58 µ mol NO2-/g/hour) and dry weight (53.92 g). The treatment of 50% shade and 0 g ZA/kg of soil of ZA fertilizer dosage increased shoot/root ratio (0.98).